Nutrition Knowledge and Practices Among Pregnant Women Attending Antenatal Care at Yangon Workers’ Hospital, Myanmar - Aung, Ye Htut; Soe, Le Thandar; Khaing, Cho Thet; Linn, Htin; B, A (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Pregnancy is a critical period during which women’s nutrition knowledge and practices can affect the health and nutrition status of both mother and child. This study aimed to assess the nutrition knowledge, practices and factors associated with nutrition practices among pregnant women attending antenatal care at Yangon Worker’s Hospital, in Tamwe Township, Yangon Region, Myanmar. A cross-sectional study was conducted from August to December 2025 using a face-to-face interview method with structured questionnaires. The study included 169 pregnant women of aged 20 to 45 years. The majority of participants (86.4%) were aged 35 years or younger. In terms of educational attainment, the largest proportion (36.1%) had completed middle school education, while the remaining participants had either primary or high school education. A small fraction of participants (1.2%) illiterate. More than half of the participants (53.3%) were in their first pregnancy, and (89.3%) were in the third trimester. The total nutrition knowledge scores were 33 and the median score (IQR) of participants was 10 (4). A total (65.7%) of the participants had good nutrition practices. Nutrition knowledge scores and ethnicity were significantly associated with nutrition practices; (AOR = 1.24, 95% CI: 1.04–1.37), and (AOR = 3.46, 95% CI: 1.12–10.67). This study highlighted the needs in nutrition education, particularly in awareness about the importance of micronutrients and culturally sensitive counseling to address food taboos for promoting healthy dietary practices and reducing preventable complications during pregnancy. Keywords Myanmar, Nutrition knowledge, Practices, Pregnant women